Coding education for elderly people - the silver code project = Nauka kodowania osób starych - projekt silver code - Jurczyk-Romanowska, Ewa (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The problem of the aging society occupies an important position in the policies of the European Union. With the development of new technologies, the progressing digitalisation, and the evolution of the information society, the digital exclusion of seniors increases. The Silver Code Project focuses on discovering new solutions to prevent this phenomenon, offering education in programming as an opportunity to boost seniors` ICT skills.
Keywords: adult education; coding competence; programming; digital exclusion; edukacja dorosłych; kompetencje ICT; programowanie; wykluczenie cyfrowe